BERANI BICARA BAHASA INGGRIS: INTERACTIVE ENGLISH CONVERSATION TRAINING TO BOOST SPEAKING CONFIDENCE AMONG CHILDREN IN PUBLIC HOUSING - Nurrahma Fatkhiyati; Tesaannisa Tesaannisa; Rizdika Mardiana; Diyantari Diyantari; Muthiya Kafa Syalika; Fasya Rakha Tsurayya; Rifa Andina Rahman (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service program aims to boost speaking confidence and mastery of emotion-expression vocabulary among 20 participants aged 9-14 year olds in the Jatinegara Kaum public housing. Using a pre-experimental one-group pretest–posttest design, the two-day intervention (on 14–15 June 2025) blended student-centered learning, contextual teaching and learning, and communicative language teaching. Activities included an Inside Out audiovisual prompt, matching games, and role-plays targeting greetings, apologies, asking for opinions, encouragement, and expressing concern. Outcomes comprised a vocabulary/expression pre- and post-test, rubric-based role-play assessments, and a post-program survey. The analyses were descriptive and supplemented by qualitative classroom observations. Participants showed gains in recognizing and using target expressions in simple sentences. The most recalled more than five new lexical items and demonstrated improved lexical accuracy, fluency, and oral participation. Overall, the short communicative intervention appears feasible and promising for strengthening basic speaking readiness and thematic vocabulary in this setting; future studies should use multi-session designs with standardized measures and a comparison group to strengthen causal inference and track retention.